2005
DOI: 10.1002/adma.200401994
|View full text |Cite
|
Sign up to set email alerts
|

Shear‐Induced Alignment in Thin Films of Spherical Nanodomains

Abstract: Nanofabrication is witnessing a rapid trend towards using self-assembled templates as a cost-effective method of generating densely patterned surfaces. In particular, templating with block copolymer (BCP) thin films, until recently an area of essentially academic interest, has become increasingly popular in the semiconductor industry. BCPs are macromolecules composed of two (a ªdiblock copolymerº, diBCP) or more chemically distinct, covalently connected, polymer chains, which are typically immiscible in bulk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
155
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(157 citation statements)
references
References 25 publications
2
155
0
Order By: Relevance
“…Order was induced through vacuum annealing above the glass transition temperature of both blocks and below the T ODT of the block copolymer. In this system, the PEP block wets the air interface, while PS wets the silicon oxide substrate [25,26], i.e., there is an asymmetric wetting condition (see schematic in Fig. 1).…”
Section: Experimental Systemmentioning
confidence: 99%
“…Order was induced through vacuum annealing above the glass transition temperature of both blocks and below the T ODT of the block copolymer. In this system, the PEP block wets the air interface, while PS wets the silicon oxide substrate [25,26], i.e., there is an asymmetric wetting condition (see schematic in Fig. 1).…”
Section: Experimental Systemmentioning
confidence: 99%
“…Since block copolymer domains nucleate at random positions with a random orientational phase, the appearance of topological defects at the interfaces of different domains is completely unavoidable, and several strategies, such as graphoepitaxy or external ordering fields, have been employed to obtain ordered hexagonal and lamellar masks with a low density of topological defects [11,12]. For example, by employing a shearing technique, Angelescu et al [13] showed that thin films of sphere-forming block copolymers can be well aligned over square-centimetre regions. Compared with thermal treatments, where the density of topological defects can hardly be reduced below 200 dislocations per square micrometre, in shear-aligned hexagonal patterns the orientational order was perfect over a 2.5 × 2.5 mm 2 area while the translational order was limited only by the presence of a reduced number of dislocations (on average six dislocations per square micrometre).…”
Section: Introductionmentioning
confidence: 99%
“…Shear alignment of thin films was shown to be very efficient on spherical and cylindrical block copolymer phases, if it is performed at a temperature between the highest of the two glass transition temperature and the order-disorder transition temperature of the diblock [80]: T g < T < T ODT . In other cases, however, a good alignment is obtained with a high defect density [81] (Fig.…”
Section: Flowmentioning
confidence: 99%